ANALISIS LEVERAGE KENAIKAN TARIF PROGRESIF DAN JAMINAN COMMUTER LINE TERHADAP TINGKAT OKUPANSI PENUMPANG (STUDI KASUS JALUR BOGOR – MANGGARAI) - Yogi Ashari; Tri Mulyani Setyowati (Institut Transportasi dan Logistik Trisakti, 2016)
Aim of the research is to review and analyse the impact of changed fares scheme in Commuter Line’s passengers. The changed fare is based on progressive tariff scheme and increment of the ticket deposit (additional amount of money will be levied on top of the fare to be paid). The sampling is taken from the densest Bogor to Manggarai service as a main transit hub to the passengers who entering Jakarta. The research is based on associative analysis with the usage of the secondary data. The secondary data in form of time series data has been collected from PT. KAI COMMUTER JABODETABEK with research period is 1 (one) month before and 1 (one) month after the new changed fares scheme is implemented. The use of price elasticity of demand (PED) model has been chosen in order to measure the effect of law of demand on the Commuter Line’s passengers. The result of the research shown that the implementation of a new changed fares scheme has impacted on the number of Commuter Line’s passengers with the price elasticity value is 1.22. The new changed fares scheme will give significant change in demand and tend to be a perfectly elastic demand that consumers have an infinite ability to switch to alternatives if the price increases. However, the influence of the new tariff scheme is much higher compare to increment of the ticket deposit. Public transportation is a derived demand which the demand is influenced to products that carried (e.g. passengers), it forced PT. KAI to do improvement and taken into consideration of new policy issuance. Despite on tariff issue, there are factors contributed such as on-time schedule, density in each railcar with the passengers, tidiness, security, service and customer satisfaction. These factors will improve service level of the commuter line service as a main alternative for public transport services that relieve road congestion.